English Teachers’ Literacy Toward Learning Outcome in Teaching English Phase a Of Elementary School - Afriyanti, Rika; Riza, Armilia; Sevrika, Hevriani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to find out the teachers’ literacy toward the learning outcome in teaching English Phase A of Elementary School. The researchers’ temporary observation found that in developing the students’ worksheet, there was misinterpretation about the focus of the elements or skills that must be taught to the students. It becomes the main reason to investigate the teachers’ literacy. To conduct the research, the researchers used qualitative approach and, the participants were selected purposively. To collect the data, the researchers interviewed the teachers by using Google form. There were four teachers who fulfilled the criteria as the respondents. There were four indicators of literacy that researchers used; literacy about the learning objectives, the contents/ materials, methods/strategy and evaluation procedures. After getting the data the researchers analyzed the data by doing six stages; organizing the data, reading the data, coding, describing, presenting and interpreting the data. Finally, the researchers found that, the teachers have well literacy toward the learning outcomes for teaching English Phase A of Elementary School because there are two indicators that gradually developed, they are teachers’ literacy about the learning objectives and the procedures in conducting evaluation/assessment and the instrument. In short, it is suggested to the stakeholders to review the policy about teaching English at Elementary School because it is the basic level and the teachers have to be able to make the students interested to learn English.